A compact 90–96 GHz 6‐bit passive vector modulator phase shifter in 28‐nm CMOS for phase array applications. Issue 1 (13th October 2022) - Deng, Biao; Pan, Dongfang; Duan, Zongming; Liu, Jie; Wu, Fang; Sun, Liguo
Abstract: This letter presents a 90–96 GHz 6‐bit digital control passive vector modulator phase shifter (PS) in a 28‐nm complementary metal–oxide–semiconductor for phase array application. In PS, a full differential directional coupler as a quadrature generator (QG) is proposed, which achieves wide bandwidth and a high‐performance orthogonal network by introducing more pole‐zero pairs. In the vector modulator, two 6‐bit binary‐weighted vector modulators, respectively scale the quadrature signal generated by QG to achieve a high‐resolution vector phase. The measured PS cover 36 0 ∘ 360^° and the minimal root mean square (RMS) phase error is 0 . 7 ∘ 0.7^° and RMS gain error 0.3 dB at 93 GHz, respectively. The fabricated PS occupies 310 × 280 μm 2 310× 280 μ m^2 excluding pads with no power consumption.